2000
DOI: 10.1002/1521-3935(20001101)201:17<2289::aid-macp2289>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of novel soluble polyimides having an unsymmetric spiro tricyclic dianhydride unit

Abstract: A novel spiro trialicyclic dianhydride, rel[1S,5R,6R]‐3‐oxabicyclo[3.2.1]octane‐2,4‐dione‐6‐spiro‐3′‐(tetrahydrofuran‐2′,5′‐dione) (DAn) was synthesized from itaconic anhydride (1) and cyclopentadiene via a Diels‐Alder reaction, nitric acid oxidation, and the subsequent dehydration with acetic anhydride. The structure of DAn was determined by NMR spectra and single crystal X‐ray diffraction. A series of soluble polyimides (PIs) having a spiro alicyclic unit in the main chain were prepared by the reactions of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 30 publications
2
66
0
Order By: Relevance
“…However, despite the excellent combined properties, their widespread applications are often limited by their poor solubility and high processing temperature, which make it impossible for most PIs to be directly processed in their imidized forms. In order to overcome these drawbacks, many efforts on chemical modifications of PIs have been made, such as introduction of flexible linkages [4][5][6], bulky units [7,8], bulky pendent substituents [9][10][11], and noncoplanar moieties [12], in the polymer backbone. Solubility of PIs can also be improved by incorporation of less symmetric structures such as ortho-or metalinked aromatic units in the main chain [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the excellent combined properties, their widespread applications are often limited by their poor solubility and high processing temperature, which make it impossible for most PIs to be directly processed in their imidized forms. In order to overcome these drawbacks, many efforts on chemical modifications of PIs have been made, such as introduction of flexible linkages [4][5][6], bulky units [7,8], bulky pendent substituents [9][10][11], and noncoplanar moieties [12], in the polymer backbone. Solubility of PIs can also be improved by incorporation of less symmetric structures such as ortho-or metalinked aromatic units in the main chain [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting polymers showed good solubility toward dipolar aprotic solvents and Py [120]. Kudo's group also successfully synthesized a series of optically active and soluble PIs having a spiro alicyclic unit in the main chain by the reactions of DAn with several diamines through a general two-step polymerization method [121][122]. In another research, they reported on a systematic investigation of the physical properties of coPIs of DAn [123].…”
Section: Polyimidesmentioning
confidence: 99%
“…Synthesis of optically active coPIs derived from DAn [119][120][121][122][123] DMF system as condensing agent. The resulting polymers were obtained in good yields with inherent viscosities ranging between 0.21 and 0.61 dL/g.…”
Section: Polyestersmentioning
confidence: 99%
“…To overcome poor solubility, many efforts on chemical modifications of PIs have been made, such as introduction of flexible linkages [24,25], bulky units or bulky pendent substituents [26][27][28][29], and noncoplanar moieties [30], in the polymer backbone. However, such groups often reduce glass transition temperature, compromising ultimate performance.…”
Section: Introductionmentioning
confidence: 99%